Kampanye Publik Tentang Manfaat Mengonsumsi Ikan pada Ibu-Ibu PKK Kelurahan Ulak Karang Utara, Kota Padang - Ninuk Purnaningsih; Vatia Dwi Rizki Ramadhani Aldina; Azzelya Permata Insani (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Fish is a source of high quality protein. Eating fish can provide health benefits because it has a high nutritional content, especially the content of eicosanpentaenoic (EPA) and docosahexaetanoic acid (DHA). The fish consumption rate by Indonesians is still low, including the fish consumption rate in Padang City, which is still low. Public campaign activities regarding the benefits of eating fish were carried out in Padang City, especially among women who were members of the Ulak Karang Utara PKK, Padang, West Sumatra. This activity has a material presentation session, a question and answer session and discussion, as well as filling out the pretest and posttest. The results of the activities that have been carried out indicate that there has been an increase in public understanding of the benefits of fish consumption. Keywords: public campaign, DHA, EPA, fish